Criminal Liability for Establishing the Criminal Impact of Russia's Armed Aggression Against Ukraine - Akimov, Mykhailo; Chugaievska, Alona; Alieksieieva-Danylenko, Yuliia; Semeniuk-Prybaten, Anna; Lytvynenko, Olha (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
Russia's aggression against Ukraine emphasised the question of criminal accountability for acts committed during the war. The research aims to study international legal norms regarding avoiding criminal penalties for developing criminal influence on Russian military operations against Ukraine. Implementing such a task involves using the scientific method of content analysis to review legal sources and specialised literature and compare existing practices and innovations in the legal sphere. The results noted that Russia's armed aggression created favourable conditions for activating criminal groups that use the unstable situation to establish their influence. Under such circumstances, establishing criminal influence has a tangible negative impact on stabilising the existing situation. To counteract such negative phenomena at the national level, there is talk of strengthening criminal responsibility for committed offences, strengthening coordination actions between law enforcement agencies, strengthening institutional capacity, and intensifying international support. Besides, the experience of some European and Asian countries, where a criminal punishment is prepared just for admitting one belongs to the criminal world. The conclusions indicate that applying such experience, however, requires caution since, in martial law, it is important to counter also other manifestations of criminal influence – corruption and abuse.